Историческая реальность и художественное мастерство поэта (FAN va JAMIYAT, 2021)
The article examines the literary genre, type, genre and genre form of the poem in the Karakalpak literature. And also given the au- thor’s conclusion of the scientific analysis of the poem, as a literary form in the poetry of I.Yusupov.